Effect of purple sweet potato (Ipomoea batatas L) extract on malondialdehyde levels of male white rat (Rattus norvegicus Wistar strain) model of atherosclerosis - Meddy Setiawan; Fakih Nadhil (AOSIS, 2019)
Cardiovascular disease is a disease caused by impaired functions of heart and blood vessel, one of those is coronary heart disease. This study aimed to identify the effect of purple sweet potato (Ipomoea batatas L) extract on MDA (Malondialdehyde) levels of male white rat (Rattus norvegicus Wistar strain) model of atherosclerosis. This research was an experimental study using Post-Test Only Control Group Design method, used 5 groups (positive control group, negative control, treatment 1, treatment 2, and treatment 3), each group contained 5 rats plus 2 reserve rats. ANOVA one way test obtained a significance of 0.00 (p <0.05). The regression test results showed the coefficient of determination R² = 0.71, which means a decrease in serum MDA levels of experimental animals is influenced by the dose of purple sweet potato extract administration as much as 71% while the remaining 29% can be influenced by factors outside the study. It can be concluded that purple sweet potato extract can affect serum MDA levels of experimental animals.